(untitled) (Research, Society and Development, 2021)
Objective: to analyze the quality of life of adolescents in cancer treatment available in the literature. Método: revisão integrativa realizada através da busca em 07 bases de dados/bibliotecas eletrônicas, no idioma inglês; português ou espanhol, com o recorte temporal de 2015 – 2019. Method: integrative revision carried out through the search in 07 databases/electronic libraries, in the English language; Portuguese or Spanish, with the time cut from 2015 - 2019. Results: 1802 publications were identified which, after applying the criteria, 13 articles were selected for this review. Results: the synthesis of the information extracted from the articles was made by means of a tool produced by the authors and which allowed the construction of the categories presented. It was observed that the quality of life domains affected varied according to the type of treatment received. Conclusion: the main domain negatively affected by cancer treatment are: social functioning and physical health, followed by emotional and school functioning. It was found that treatment only with surgery appears to be the treatment associated with higher quality of life scores.